P. G. Carey, A Digest of the Ordinances of the Borough of Phoenixville, Pa. at 135, Parks § 1.4 (1906) - (:unkn) unknown (General Publisher, 1906)
Prohibited carry of fire-arms, shooting birds, throwing stones or other missiles within Reeves Park.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES